Training to Create Digital Learning Media through Canva and Camtasia - Dania, Rizki Firdausi Rachma; Suherdi; Wolor, Christian Wiradendi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
The government has developed the online distance learning process since 2014 through the Indonesian Open and Integrated Online Learning program (PDITT). Then the Covid-19 pandemic has occurred since 2020, forcing the implementation of online learning activities to be unavoidable for the continuity of the implementation of learning activities at all levels of education, including at the vocational level. So far, implementing online learning activities often needs to run optimally. It happens because teachers have yet to be able to take advantage of various applications such as Camtasia and Canva to create targeted online learning media. Therefore, this community service is carried out so that teachers can use applications like Canva and Camtasia optimally. It is hoped that after participating in training activities carried out by the dedicated team from UNJ, teachers at SMK 50 and SMK 10 can make learning media in the form of communicative and attractive material slides and learning videos so that they can increase the desire to learn and the level of understanding of students.